Affinity ranking of phage-displayed peptides: enzyme-linked immunosorbent assay versus surface plasmon resonance - Lunder, Mojca (Acta chimica slovenica, 2008)
Peptides with particular affinity and specificity for variety of targets are selected through panning procedure from random peptide phage display libraries. Efficiency and convenience of enzyme linked immunosorbent assay (ELISA) and surface plasmon resonance (SPR) for screening and evaluating peptide-displaying phage clones were compared using streptavidin as a model protein target.
Keywords: bakteriofagni kloni; encimskoimunski test; peptidi; plazmonska resonanca